2018
DOI: 10.4049/jimmunol.1701305
|View full text |Cite
|
Sign up to set email alerts
|

ICOS Signaling Controls Induction and Maintenance of Collagen-Induced Arthritis

Abstract: ICOS is a key costimulatory receptor facilitating differentiation and function of follicular helper T cells and inflammatory T cells. Rheumatoid arthritis patients were shown to have elevated levels of ICOS T cells in the synovial fluid, suggesting a potential role of ICOS-mediated T cell costimulation in autoimmune joint inflammation. In this study, using ICOS knockout and knockin mouse models, we found that ICOS signaling is required for the induction and maintenance of collagen-induced arthritis (CIA), a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…3‐bromopyruvate also improved arthritis in the SKG model probably via induction of Tregs and reductions in dendritic cells as shown in isolated splenocytes (Okano et al, ). Similar results were obtained with 3‐bromopyruvate (Figure ) in a collagen‐induced arthritis model (Panneton, Bagherzadeh Yazdchi, Witalis, Chang, & Suh, ). Abboud et al tested 2‐DG, a competitive inhibitor of hexokinase, in the serum induced arthritis model and observed improved joint inflammation and reduced development of pathogenic autoantibodies in a preventive treatment scheme (Abboud et al, ).…”
Section: Introductionsupporting
confidence: 81%
“…3‐bromopyruvate also improved arthritis in the SKG model probably via induction of Tregs and reductions in dendritic cells as shown in isolated splenocytes (Okano et al, ). Similar results were obtained with 3‐bromopyruvate (Figure ) in a collagen‐induced arthritis model (Panneton, Bagherzadeh Yazdchi, Witalis, Chang, & Suh, ). Abboud et al tested 2‐DG, a competitive inhibitor of hexokinase, in the serum induced arthritis model and observed improved joint inflammation and reduced development of pathogenic autoantibodies in a preventive treatment scheme (Abboud et al, ).…”
Section: Introductionsupporting
confidence: 81%
“…In autoimmune disease models, ICOS has been shown to play important roles in supporting the pathogenic functions of Teff cells. We have shown that ICOS signaling is critical for the induction and maintenance of collagen‐induced arthritis . As expected, ICOS‐PI3K signaling is critical to induce pathogenic antibodies during the disease induction phase.…”
Section: Icos Signaling In Teff and Treg Subsetssupporting
confidence: 78%
“…This is consistent with its minimal impact on initial T‐cell expansion in ICOS‐deficient mice . Despite the overall similarities in the T‐cell stimulatory functions shared between ICOS and CD28, ICOS has critical non‐redundant functions in multiple immune responses …”
Section: Icos and Icos Ligandsupporting
confidence: 72%
See 2 more Smart Citations